The emperor's new dystrophin: finding sense in the noise. Issue 7 (July 2015) - Wilton, S.D.; Veedu, R.N.; Fletcher, S.
Highlights Dystrophin restoring therapy should increase dystrophin expression after treatment. Restoration of functional dystrophin will take months to result in clinical benefit. Eteplirsen-treated DMD boys show slower disease progression than predicted from the natural history.